Evolutionary Ann Design Using Improved Selection Method - G. V. R. Sagar; M. Siva Sathyanarayana (New Approaches in Engineering Research Vol. 14, 2021)
Study Objective: The important issue in Evolutionary Algorithms (EAs), is time-complexity analysis. Here, 1. To consider the concept of take-overtime to obtain the mean hitting time of EA. i.e. the concept of the takeover time is generalized rather than a selection of operator alone. This generalization is applied to benchmark problems like N-Bit parity. For various input sizes N, the time complexity in terms of number of generations is estimated. To develop an empirical model is also generated for proposed EA using statistical tool. To apply the proper selection method to find the take-overtime.